PELATIHAN KOMPUTER UNTUK SISWA TK KRISTEN 1 SATYA WACANA SALATIGA MELALUI PERMAINAN EDUKASI ONLINE - Yessica Nataliani; Krismiyati Krismiyati; Erwien Christianto; Theophilus Wellem; Anton Hermawan; Agustinus Fritz Wijaya; Imanuel Susanto (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
This community service activity was carried out to facilitate the needs of the Satya Wacana Christian 1 Kindergarten students in Salatiga as an effort to introduce kindergarten students to computers. Students usually only know cell phones or tablets but rarely use computers. This training activity was attended by kindergarten students with an age range of 5-6 years and was carried out in four stages, namely the planning stage, the preparation stage, the implementation stage, and the evaluation stage. The activity involved a team of lecturers from the Faculty of Information Technology, Satya Wacana Christian University as activity facilitators and three teachers from Satya Wacana Christian 1 Kindergarten. This program was conducted at the Computer Laboratory of the Faculty of Information Technology, Satya Wacana Christian University, which included introducing computer equipment, opening websites, and practicing using a mouse through online educational games. The online educational games used in this activity are mixing colors, counting, getting to know water transportation, getting to know 2D shapes, knowing numbers, and assembling puzzles. The activity went well, where the students could recognize and operate computers, especially using the mouse, and learn through the online educational games.